Are Chinese Acquirers Discriminated against in Cross‐border Mergers and Acquisitions? An Analysis Based on Covered Transactions Filed with CFIUS. Issue 2 (29th March 2020) - Chen, Sichong; Li, Wenxue; Wang, Qi
Abstract: This study employs a sample of covered transactions filed with the Committee on Foreign Investment in the United States (CFIUS) of cross‐border mergers and acquisitions targeting American companies based on publicly available news reports and announcements to examine the heterogeneity hypothesis in the CFIUS review process. A comparative analysis of case studies and an empirical analysis of logit regressions are performed. We also explore how CFIUS reviews may have an impact on corporations' future mergers and acquisitions decisions in a panel data model setting. The results show that both unfair treatment in CFIUS review and the deterrent effect of CFIUS interventions have contributed to the recent sharp decline in China's direct investment in the US.